Transformations of Magistracy in Russia - E. A. Opfer (Moscow Polytechnic University, 2021)
The system of master education in Russia in now being transforming. It is influenced by the global trends in higher education and stakeholders' needs. The goal of this research is to find out the substantial transformations in Russian magistracy and to underline the main trends at the current stage. To achieve the goal, the relevant literature and regulations were reviewed. Besides, we used the results of all-Russian survey "Russian Master's Early Growth" devoted to Russian magistracy, the winner of the program "Scholarship program by Vladimir Potanin".The research gives the analyses of transformations of magistracy in Russia in three vectors: changes in educational paths, staffing and design of master programs. The results of the research can be used by university management while designing master's programs.